THE RISK OF REPRODUCTIVE LOSS AND MORPHOFUNCTIONAL CHANGES OF THE PLACENTA - Rozikova Dildora Kodirovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Miscarriage is a significant cause of reproductive losses in early pregnancy, with 20-30 million abortions reported worldwide annually [3, 4]. Literature suggests that 25-30% of pregnancies end in miscarriage [2, 3]. Some studies associate miscarriage with diverse infectious pathologies, emphasizing the increasing role of conditionally pathogenic microorganisms, viral infections, sexually transmitted diseases, and fungi. Notably, cytomegalovirus infection is implicated in early miscarriages [1,3]. The etiology and pathogenesis of recurrent abortions and non-developing pregnancies are still under study, with the theory lagging behind the practical needs of medicine [5].